Efecto de la Biblioteca Digital Nutrinfo para mejorar la educación nutricional en estudiantes de la Facultad De Industrias Alimentarias de la Universidad Nacional de la Amazonía Peruana Iquitos – 2024 - Rojas Guerrero, Nady Fatima (2025)
The present research aimed to determine the effect that the application of the Nutrinfo Digital Library could have on the improvement of nutrition education with students of the Faculty of Food Industries - UNAP in the city of Iquitos in the year 2024, it was developed through an experimental methodology of quasi-experimental type for which two groups were formed (experimental and control), where we sought to find the effect of the Nutrinfo Digital Library, The sample was of a census type where we worked with 100% of the population, to whom we applied the technique of the survey and indirect observation, applying a questionnaire and a test, reaching the following results: 72.0% of the students found the use of the digital library Nutrinfo to be fair, and the nutritional education was improved from 64.5% of deficient in the control group to 41.9% of good in the experimental group, data that were corroborated by applying the nonparametric statistical test of ranges with Wilcoxon sign, where the p-value data were less than 5%, this shows that the results of the students in the experimental and control group at the end of the experiment are different in terms of nutrition education, so it is claimed that the results were significant; concluding that the use of the Nutrinfo Digital Library improves nutrition education in students of the Faculty of Food Industries - UNAP, Iquitos - 2024.